Common Fixed Point Results in Metric-Type Spaces - Jovanović, Mirko; Kadelburg, Zoran; Radenović, Stojan (Fixed point theory and applications (Hindawi Publishing Corporation), 2010)
Several fixed point and common fixed point theorems are obtained in the setting of metric-type spaces introduced by M. A. Khamsi in 2010.